Full-scale simulation in German medical schools and anesthesia residency programs : Status quo - Baschnegger, H.; Meyer, O.; Zech, A.; Urban, B.; Rall, M.; Breuer, Georg; Prueckner, S. (Anaesthesist, 2017)
Simulation has been increasingly used in medicine. In 2003 German university departments of anesthesiology were provided with a full-scale patient simulator, designated for use with medical students. Meanwhile simulation courses are also offered to physicians and nurses. Currently, the national model curriculum for residency programs in anesthesiology is being revised, possibly to include mandatory simulation training.To assess the status quo of full-scale simulation training for medical school, residency and continuing medical education in German anesthesiology.All 38 German university chairs for anesthesiology as well as five arbitrarily chosen non-university facilities were invited to complete an online questionnaire regarding their centers' infrastructure and courses held between 2010 and 2012.The overall return rate was 86 %. In university simulation centers seven non-student staff members, mainly physicians, were involved, adding up to a full-time equivalent of 1.2. All hours of work were paid by 61 % of the centers. The median center size was 100 m(2) (range 20-500 m(2)), equipped with three patient simulators (1-32). Simulators of high or very high fidelity are available at 80 % of the centers. Scripted scenarios were used by 91 %, video debriefing by 69 %. Of the participating university centers, 97 % offered courses for medical students, 81 % for the department's employees, 43 % for other departments of their hospital, and 61 % for external participants. In 2012 the median center reached 46 % of eligible students (0-100), 39 % of the department's physicians (8-96) and 16 % of its nurses (0-56) once. For physicians and nurses from these departments that equals one simulation-based training every 2.6 and 6 years, respectively. 31 % made simulation training mandatory for their residents, 29 % for their nurses and 24 % for their attending physicians. The overall rates of staff ever exposed to simulation were 45 % of residents (8-90), and 30 % each of nurses (10-80) and attendings (0-100). Including external courses the average center trained 59 (4-271) professionals overall in 2012. No clear trend could be observed over the three years polled. The results for the non-university centers were comparable.Important first steps have been taken to implement full-scale simulation in Germany. In addition to programs for medical students courses for physicians and nurses are available today. To reach everyone clinically involved in German anesthesiology on a regular basis the current capacities need to be dramatically increased. The basis for that to happen will be new concepts for funding, possibly supported by external requirements such as the national model curriculum for residency in anesthesiology.
EVALuna2:16741